PERTUMBUHAN DAN METABOLIT SEKUNDER Chlorella sorokiniana YANG DIKULTUR PADA LIMBAH CAIR TAHU - Devy Susanty; Ade Ayu Oksari (JBIO: jurnal biosains (the journal of biosciences), 2022)
The utilization of waste as a culture medium can reduce production costs and become one of the ways to handle the waste. Tofu wastewater is one of the most produced wastes. It has potential as a growing medium for Chlorella sorokiniana because it contains macronutrients such as nitrogen, phosphorus and potassium. This study aimed to determine the growth of C. sorokiniana in tofu liquid waste media (LCT), to determine the secondary metabolite content and total phenolic content of C. sorokiniana ethanol extract from cultured tofu waste media. C. sorokiniana was cultured at various concentrations of 15, 20, 25, and 30% LCT media. The best growth was obtained on LCT media with a concentration of 30%. The C. sorokiniana biomass obtained from cultivation on the best media was extracted using the repeated maceration method with solvent. The phytochemical test identified the secondary metabolites in the extract. The test results showed the presence of a class of alkaloid compounds, flavonoids, tannins and terpenoids. The total phenolic test was carried out by Folin Ciocalteau reagent, and the results obtained was 14,16 mg GAE/g. The total flavonoids of the extract were 40.59 mg QE/g.